Microbial recognition regulates intestinal epithelial growth in homeostasis and disease. (15th May 2021) - Ferguson, Meghan; Foley, Edan
Abstract : The intestine is constantly exposed to a dynamic community of microbes. Intestinal epithelial cells respond to microbes through evolutionarily conserved recognition pathways, such as the immune deficiency (IMD) pathway of Drosophila, the Toll‐like receptor (TLR) response of flies and vertebrates, and the vertebrate nucleotide‐binding oligomerization domain (NOD) pathway. Microbial recognition pathways are tightly controlled to respond effectively to pathogens, tolerate the microbiome, and limit intestinal disease. In this review, we focus on contributions of different model organisms to our understanding of how epithelial microbe recognition impacts intestinal proliferation and differentiation in homeostasis and disease. In particular, we compare how microbes and subsequent recognition by the intestine influences barrier integrity, intestinal repair and tumorigenesis in Drosophila, zebrafish, mice, and organoids. In addition, we discuss the importance of microbial recognition in homeostatic intestinal growth and discuss how immune pathways directly impact stem cell and crypt dynamics. Abstract : Intestinal epithelial cells respond to microbes through evolutionarily conserved immune deficiency (IMD), Toll‐like receptor (TLR), and nucleotide‐binding oligomerization domain (NOD) pathways. In this review, we highlight how these pathways influence barrier integrity, homeostatic proliferation, differentiation and directly modify progenitor and crypt dynamics. In addition, we discuss the importance of microbe recognition in cell survival, injury, repair, and tumorigenesis in disease.